Technology and Media Integration in English Language Teaching within the TEIL Framework - Hakim, Taufiqul; Putra, Aidil Syah; Syaktanani, Keyne Cahaya; Yanti, Marchella Legie (PROJECT (Professional Journal of English Education), 2026)
This study examines the use of technology and digital media in English language learning within the Teaching English as an International Language (TEIL) framework, focusing on understanding students' experiences and perceptions. A qualitative research approach was employed involving 15 first-semester students from the English Education program at Universitas Muhammadiyah Tangerang. Data were collected through semi-structured interviews then analyzed using thematic analysis to identify recurring patterns and themes. Results revealed that students actively utilize various digital platforms including video streaming services (YouTube, Netflix), social media (Twitter/X, TikTok, Instagram), learning applications (Duolingo, Google Translate), online games, and music streaming platforms for authentic language exposure. Students perceived significant pedagogical benefits including increased motivation, improved language skills particularly in listening and vocabulary, better material comprehension through multimodal content, exposure to diverse English varieties and accents, and valuable opportunities for real international communication practice. However, notable challenges emerged including digital distraction, unreliable internet connectivity, and comprehension difficulties with fast-paced authentic content, highlighting the need for systematic instructional support to maximize technology's potential in TEIL contexts.